Enforcing Wagering Contracts - Wellik, Sid (Victoria University of Wellington Law Review, 1999)
In Lipkin Gorman v Karpnale Ltd [1991] 2 AC 548, 560 (HL), Lord Goff stated that placing a bet is in law a gift and that when winnings are paid a gift is received. New Zealand legislation excludes contractual enforcement of wagering transactions, except in licensed casinos. This article explores whether Lord Goff's analysis and current New Zealand legislation are an appropriate legal state of affairs for gaming transactions. In doing so, the author looks at the Department of Internal Affairs' Review of Gaming – A Discussion Document 1995 and concludes that the new policy directions in making gaming contracts enforceable encourages rights of redress for the consumer.